1996
DOI: 10.1097/00042560-199604010-00001
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the CD2 Receptor Pathway Induces Apoptosis in Human T Lymphotropic Virus Type I-Infected Cell Lines

Abstract: We demonstrate that CD2 receptor engagement, but not CD3 crosslinking, induces apoptosis in lymphocytes transformed by human T-cell lymphotrophic virus type I (HTLV-I). Mitogenic pairs of anti-CD2 monoclonal antibodies inhibited [3H]thymidine incorporation from 25 to 62% in CD2+ HTLV-I-infected lymphocytes. This inhibition was associated with a 20-40% reduction in cell number and viability over a 3-day period, morphologic evidence of apoptosis, and irreversible DNA fragmentation. While cyclosporin A abrogated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Fresh leukemic cells from ATL patients as well as HTLV-1-transformed T-cell lines were reported to be sensitive to CD95 mediated (Debatin et al, 1990(Debatin et al, , 1993 and activation induced cell death (Guyot et al, 1996;Leno et al, 1995). Apoptotic eects of HTLV-1 infection have been reported in conjunction with the associated degenerative disorders (Kalden and Gay, 1994;Muller et al, 1995;Seto et al, 1995;Yoshiki, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Fresh leukemic cells from ATL patients as well as HTLV-1-transformed T-cell lines were reported to be sensitive to CD95 mediated (Debatin et al, 1990(Debatin et al, , 1993 and activation induced cell death (Guyot et al, 1996;Leno et al, 1995). Apoptotic eects of HTLV-1 infection have been reported in conjunction with the associated degenerative disorders (Kalden and Gay, 1994;Muller et al, 1995;Seto et al, 1995;Yoshiki, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have demonstrated that HTLV-I-infected T cells can be induced to undergo apoptosis. Fresh mononuclear cells from ATL patients are activated (CD25 Ď© ) and sensitive to CD95-mediated apoptosis (55), and IL-2-dependent HTLV-Iinfected T-cell lines are susceptible to anti-CD95-induced (54) and activation (CD2)-induced apoptosis (103). These apparently conflicting results may be due in part to differences in anti-CD95 antibodies and the concentrations used.…”
Section: Programmed Cell Death In Htlv-i-infected T Cellsmentioning
confidence: 99%
“…This would then lead to enhanced viral production and possibly to infection of more T cells. Whereas antibody-mediated activation of the CD2 pathway may result in apoptosis in HTLV-I-infected T cells (103,305), it is unclear whether this occurs after CD2-CD58 interaction.…”
Section: Activation Of Non-virus-specific T Cellsmentioning
confidence: 99%
“…Recent data have shown that human Tlymphotropic virus type 1 (HTLV-1) interferes with Fas-mediated apoptosis. It has been suggested that a modification of the apoptotic pathway may be a pathogenic mechanism in HTLV-1-related lymphoproliferative, neurological and autoimmune diseases in humans (Arai et al, 1998;Copeland et al, 1994;Debatin et al, 1990;Guyot et al, 1996) and animal models (Kishi et al, 1997).…”
Section: Introductionmentioning
confidence: 99%